Treatment of Fourth Metatarsal Brachymetatarsia Using Distraction Osteogenesis with External Fixator: Surgical Techniques, Outcomes and Complications - Xing Li; Jianming Gu; Yong Wu; Yan Wang; Xiaofeng Gong; Ning Sun; Ying Li; Liangpeng Lai; Wenjing Li; Heng Li; Xiaosong Yang; Xiaotian He; et al. (Orthopaedic Surgery)
Objective Surgical technique in distraction osteogenesis for the treatment of brachymetatarsia can influence the final prognosis. However, there are currently no standardized guidelines for surgical procedures and complication management. The aim of this study is to investigate the effect of bone lengthening with external fixation by minimally invasive osteotomy based on Ilizarov technique in the treatment of congenital brachymetatarsia. Methods A retrospective study was conducted on patients with congenital brachymetatarsia treated by metatarsal lengthening, from June 2017 to December 2020. There were 11 patients with 17 shorted fourth metatarsals, including 10 females and 1 male, with age of 24.6 ± 4.5 years (16–31 years). Six patients were bilaterally involved. Orthofix external fixator mini track was installed through dorsal approach and the fourth MTP joints were temporarily fixed by Kirschner wire. Bone lengthening was performed after a minimally invasive osteotomy at the proximal metatarsals. American Orthopedic Foot and Ankle Society (AOFAS) lesser metatarsophalangeal‐interphalangeal (MTP‐IP) scores, metatarsal length, complications were recorded. Statistical comparison was performed using the paired t‐student test for pre‐ and postoperative AOFAS MTP‐IP scores. Results Patients were followed up for 55 ± 10.8 months. The mean length of the fourth metatarsal bone was 49.9 ± 2.9 mm preoperatively. The mean metatarsal shortage was 18.8 ± 3.1 mm. The mean lengthening achieved was 19.8 ± 3.3 mm, with a lengthening ratio of 39.7% ± 6.6%. The lengthened callus ossified completely at 3–4 months after operation. All patients were satisfied with the results of lengthening. The AOFAS scores were improved significantly from 83.7 ± 4.2 preoperatively to 93.2 ± 2.7 postoperatively (t = −10.27, p < 0.001). One patient with traumatic metatarsophalangeal joint subluxation was treated by joint reduction and Kirschner wire fixation. One patient had metatarsophalangeal joint release and Kirschner wire fixation due to flexion contracture. Pin tract infections were controlled by wound care and antibiotics in 6 patients. All patients had no nonunion, necrosis of toes, and sensory disturbance of toes. Conclusion Metatarsal lengthening by minimally invasive osteotomy with external fixator had satisfactory results in the treatment of congenital brachymetatarsia.